characterization of the coffee farms by quality of coffee beverage and some environmental and agronomical conditions - Orozco Cortés, Nathalia; Guacas Silvestre, Alejandro; Bacca, Tito (Revista de Ciencias Agrícolas, 2011)
Due to the need to generate alternatives wich let to assure the quality and differentiation about Colombian coffee, has planted the following investigation with the object the characterize the coffee farms by quality of coffee beverage and some environmental and agronomical conditions. 30 farms certificates with the seal of special coffee Just Commerce FLO (Fairtrade Labelling Organization) were evaluated, located the municipality of Pereira in a rank altitudinal between 1250 and 1800 m.a.s.l., with different units of soil and with variety coffee cultivations Colombia and Caturra. Of each farm was taken a dry parchment coffee sample that was carried to the Laboratory of analysis as coffee of the Committee of Coffee of Risaralda to determine the organoleptic characteristics as: fragrance, acidity, body, flavor, residual flavor, balance, clean cup, sweet and score of the taster. By means of an analysis of multiple correspondences was concluded that the altitude, the variety and the unit of soil of each farm studied do not they have association with the parameters of quality of the beverage of the coffee. Also it was possible to determine that in the 70% of the farms was possible to produce coffee with good sensory characteristics of the beverage.